Integrating microbiome and metabolome revealed microbe-metabolism interactions in the stomach of patients with different severity of peptic ulcer disease - Wang, Chao; Yu, Xiao; Lin, Hongqiang; Wang, Guoqiang; Liu, Jianming; Gao, Chencheng; Qi, Mingran; Wang, Dan; Wang, Fang (Frontiers in Immunology, 2023)
Background: Peptic ulcer disease (PUD) is a multi-cause illness with an unknown role for gastric flora and metabolism in its pathogenesis. In order to further understand the pathogenesis of gastric flora and metabolism in PUD, this study used histological techniques to analyze the microbiome and metabolome of gastric biopsy tissue. In this paper, our work described the complex interactions of phenotype-microbial-metabolite-metabolic pathways in PUD patients at different pathological stages. Results: Our work found reduced diversity of gastric flora in patients with PUD. PUD patients at different pathological stages presented their own unique flora, and there were significant differences in flora phenotypes. Coprococcus_2, Phenylobacterium, Candidatus_Hepatoplasma, and other bacteria were found in the flora of people with chronic non-atrophic gastritis (HC). The representative flora of mucosal erosion (ME) had uncultured_bacterium_c_Subgroup_6, Sphingomonadaceae, Xanthobacteraceae, and uncultured_bacterium_f_Xanthobacteraceae. In comparison, the characteristic flora of the PUD group was the most numerous and complex, including Ruminococcus_2, Agathobacter, Alistipes, Helicobacter, Bacteroides and Faecalibacterium. Metabolomics identified and annotated 66 differential metabolites and 12 significantly different metabolic pathways. The comprehensive analysis correlated microorganisms with metabolites at different pathological stages and initially explored the complex interactions of phenotype-microbial-metabolite-metabolic pathways in PUD patients at different pathological stages. Conclusion: Our research results provided substantial evidence to support some data on the analysis of the microbial community and its metabolism in the stomach, and they demonstrated many specific interactions between the gastric microbiome and the metabolome. Our study can help reveal the pathogenesis of PUD and indicate plausible disease-specific mechanisms for future studies from a new perspective.